2019
DOI: 10.1038/s41598-019-40252-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting heat shock protein expression to develop a non-invasive diagnostic tool for breast cancer

Abstract: Leveraging the unique surface expression of heat shock protein 90 (Hsp90) in breast cancer provides an exciting opportunity to develop rapid diagnostic tests at the point-of-care setting. Hsp90 has previously been shown to have elevated expression levels across all breast cancer receptor subtypes. We have developed a non-destructive strategy using HS-27, a fluorescently-tethered Hsp90 inhibitor, to assay surface Hsp90 expression on intact tissue specimens and validated our approach in clinical samples from bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In [ 15 ], the authors devised a strategy using HS-27, for determining Hsp90 expression from tissue specimens for the diagnosis of breast cancer. Findings revealed that the HS-27 value was the highest in tumour tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 15 ], the authors devised a strategy using HS-27, for determining Hsp90 expression from tissue specimens for the diagnosis of breast cancer. Findings revealed that the HS-27 value was the highest in tumour tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The protein levels of HSP90AA1 were significantly elevated in tumors compared to normal mammary glands ( Vartholomaiou et al, 2017 ). This was also observed in a breast cancer diagnostic study; they used fluorescein HS-27 in combination with HSP90 to provide a cost-effective and easy-to-implement diagnostic platform ( Crouch et al, 2019 ). The biochemical assessment may lead to savings of almost 50% compared with medical imaging techniques ( Robertson et al, 1995 ).…”
Section: Discussionmentioning
confidence: 72%
“…In addition to intrinsic fluorescence contrast, several promising fluorescent molecular probes have been explored to improve tumor identification in tumor margins. For example, our lab has explored the imaging of fluorescence labeled heat shock protein 90 (Hsp90) on core needle biopsies for rapid breast cancer diagnosis [38,39]. By modifying our device to perform fluorescence imaging, our device can generate co-registered brightfield and fluorescence images [40].…”
Section: Discussionmentioning
confidence: 99%